2019
DOI: 10.1177/1538574419868040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gender on Outcomes Following Abdominal Aortic Aneurysm Repair

Abstract: Objective: The purpose of this study is to use a large, nationally representative vascular database to assess differences in patient characteristics, aortic neck anatomy, and outcomes between men and women following open (open aneurysm repair [OAR]) and endovascular (endovascular aneurysm repair [EVAR]) abdominal aortic aneurysm (AAA) repair. Methods: Patients undergoing AAA repair from 2003 to 2018 in Vascular Quality Initiative were identified and stratified by procedure (EVAR vs OAR). Thirty-day mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…56,57 Sex specific differences in kidney injury may also result from embolism, anatomical differences (e.g., closer proximity of the renal arteries, orificial disease, angulation), selection of suboptimal endovascular strategies (e.g., renal artery coverage), or iatrogenic injury (e.g., contrast nephropathy or intimal damage). 39,58 Renal protective strategies such as pre-hydration, avoidance of renotoxic medication, judicious use of contrast, and a careful operative approach with renal preservation, can greatly reduce the risk of renal injury and should be strictly implemented for women. 58,59 EVAR access complications are associated with four times the odds of peri-operative death, while conversion to open, rather than planned cutdown, is associated with a higher risk of major complication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…56,57 Sex specific differences in kidney injury may also result from embolism, anatomical differences (e.g., closer proximity of the renal arteries, orificial disease, angulation), selection of suboptimal endovascular strategies (e.g., renal artery coverage), or iatrogenic injury (e.g., contrast nephropathy or intimal damage). 39,58 Renal protective strategies such as pre-hydration, avoidance of renotoxic medication, judicious use of contrast, and a careful operative approach with renal preservation, can greatly reduce the risk of renal injury and should be strictly implemented for women. 58,59 EVAR access complications are associated with four times the odds of peri-operative death, while conversion to open, rather than planned cutdown, is associated with a higher risk of major complication.…”
Section: Discussionmentioning
confidence: 99%
“…3). 7,25,36,38,39 An increased risk of arterial injury for women undergoing EVAR was also observed (OR 3.02 [1.62 e 5.65], p < .001, I 2 ¼ 49). 4,19,33,36 Operative time (minutes) was statistically significantly lower for women compared with men for OAR (MD À14.98 [À18.45 e À11.51], p < .001, I 2 ¼ 0), and not statistically significantly different for EVAR (MD 4.33 [À0.99 e 9.65], p ¼ .11, I 2 ¼ 79) (Supplementary Table S4).…”
Section: Mortality Outcomesmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, women present for repair at a slightly advanced mean age relative to men, 18 are more likely to have smaller diameter arteries, 19 and are more likely to have a hostile neck. 20 Females on average have less renal parenchymal volume and thus the effect of the same contrast, devices and manipulation near the renal artery orifices is more impactful. Baseline renal insufficiency was a significant harbinger of ARI (OR 2.28), long-term renal decline (HR 1.31) and new onset dialysis requirement (OR 6.33) after EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity might be explained by the higher peri-operative mortality in women undergoing open surgery, because no such difference was found in pts undergoing EVAR [131]. In contrast, Locham et al found in the Vascular Quality Initiative (2013-2018, 9,263 open surgery -73% men and 40,950 EVAR -81% men), that unfavorable neck anatomy occurs more frequently in women compared to men [132]. Women were also at an increased risk of developing major complications, particularly following EVAR, received more aortic extensions and more contrast volume.…”
Section: Gender Differences In Aortoiliac Repairmentioning
confidence: 95%